2011
DOI: 10.1002/acr.20448
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of a multidisciplinary team care program with usual care in patients with systemic sclerosis

Abstract: Results. Twenty-eight patients were assigned to the intervention group (mean age 53.9 years, 15 of 28 with diffuse SSc) and 25 were assigned to the control group (mean age 51.7 years, 15 of 25 with diffuse SSc). Twenty-five patients (89%) in the intervention group completed the treatment program. At 12 weeks, there was a significantly greater improvement in grip strength (2.2 versus ؊1.8 kg; P ‫؍‬ 0.001), MMO (1.4 versus ؊0.9 mm; P ‫؍‬ 0.011), 6MWD (42.8 versus 3.9 meters; P ‫؍‬ 0.021), and HAQ score (؊0.18 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 43 publications
1
61
2
2
Order By: Relevance
“…Three studies, all RCTs, met the predefined score for high quality (Table 2) (24,25,29,42). At least half of the study-reporting items were met in 87% of the studies (n 5 20), with item 8, relating reporting of important adverse events, being scored less frequently (n 5 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies, all RCTs, met the predefined score for high quality (Table 2) (24,25,29,42). At least half of the study-reporting items were met in 87% of the studies (n 5 20), with item 8, relating reporting of important adverse events, being scored less frequently (n 5 4).…”
Section: Resultsmentioning
confidence: 99%
“…Schouffoer et al (29) reported that a 12-week multidisciplinary team-care program compared to usual outpatient care resulted in medium to large significant positive effects in limitations in activities, measured with the 6-minute walking test and the Scleroderma Health Assessment Questionnaire, medium effects on maximal mouth opening, and large effects on grip strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that the 12-week daily multidisciplinary care program was more effective than regular outpatient care with regard to significant improvement in grip strength, mouth opening, gait, and quality of life after 12 weeks, whereas the results in other followed parameters showed no difference between the intervention and control group. At the end of the follow-up period, after 24 weeks, only improvement in grip strength was maintained [18].…”
Section: Comprehensive Physical Therapy For Physical And/or Psychologmentioning
confidence: 99%